Assessment of the relationship between dependency scores and carbon monoxide levels in expiratory air of smokers - Usame Velioğlu; Tuğba Aktaş; Cemil İşık Sönmez; Duygu Ayhan Başer (SERNEV, 2017)
Introduction: Measurementof carbon monoxide (CO) levels in the expiratory air is frequently used in thediagnosis, treatment and follow-up stages of smoking dependence. Since the COis excreted from the body within 24 hours after quitting cigarettes, theimmediate positive effect of quitting is motivating for patients. This studyaimed to evaluate the relationship between the CO levels in the expiratory airof smokers and their Fagerström nicotine addiction scores. Methods:Thestudy included a total of 1942 people who applied to the Family PhysicianSmoking Cessation Clinic at the Düzce University Medical Faculty between June2015 and February 2016. The Fagerström Test for Nicotine Dependence (FTND) wasapplied and CO measurement of expiratory air was performed using the piCOSmokerlyzer® device. The relationship between the nicotine dependence of thepatients and the results of the CO measurements in their expiratory air wasinvestigated. The SPSS 20.0 program was used in the analysis of the data.Results:Ofthe total, 1339 (%68,9) of the patients were male and 603 (%31,1)'i werefemale. The ages of the sampling group ranged from 15 to 87 and the average agewas 37,3±11,9. The FTND levels of the participants were very low in 198(%10,2), low in 430 (%22,2), moderate in 326 (%16,8), high in 621 (%31,9) andvery high in 367 (%18,9). There was a positive correlation between the COresults and FTND scores (r = 0.293; p≤ 0.001).Conclusion: Carbonmonoxide is a toxic gas that causes cell death by reducing oxygen to thetissues. The negative effects are clearly seen in smokers. A meaningfulpositive relationship was found between the respiratory CO levels and theFagerström scores in our study. Despite rapid CO release, the expiratory air COmeasurement is a quick and easy procedure in standing patient conditions. Therapid excretion of the body allows the expiratory air CO levels to rapidlyreturn to normal after smoking cessation in patients. This affects themotivation of patients positively.